الإسكان الحضري وعلاقتھا بالتھیئة الحضریة - حسام الدين، محدة, شوشاني عبيدي، سليم (university of Eloued جامعة الوادي, 2016)
ملخص الدراسة بالعربية : إن التهيئة الحضرية هي مختلف البرامج والسياسات التي تسطرها الجهات المختصة لتنظيم المجال الحضري ، بما في ذلك عملية الإسكان الحضري الذي هو عبارة عن المسكن والمحيط الموجود فيه، والذي يتوفر على المراكز الخدمية الأصلية الضرورية ، والتي توفر الحياة الاجتماعية السليمة لأفراد المجتمع ، وبذلك فان التهيئة الحضرية هي الكفيلة بتوفير هذه الحاجيات والمرافق وإذا غابت غابت معها شروط الراحة والرفاهية . إن سبب اختيار هذا الموضوع يتجلى في طفو مشكلة التهيئة الحضرية المتعلقة بالإسكان على رأس القضايا التي ظهرت في بلادنا ، وكذلك بروز العديد من المشكلات التي تتعرض لها المدينة الجزائرية ، كما تتجسد الأهمية في أن مشكلة الإسكان والتهيئة الحضرية تعد من القضايا التي تؤرق الدولة والمسئولين بحكم ارتباطها بحاجات الإنسان الضرورية . وبحكم أن هذا الموضوع ينطلق من واقع إجتماعي فإن المنهج الوصفي التحليلي هو أنسب المناهج لموضوع دراستنا هذه ، حيث تسعى هذه الدراسة لوصف خصائص مجتمع البحث ومحاولة إبراز العلاقة بين مختلف المتغيرات ، وقد أجريت هذه الدراسة في حي 08 ماي 1945 بالوادي ، وبالتحديد في تجمع سكني يضم 1388 مسكن ، الذي يقع في الجهة الشرقية من الحي ، ومنه فإن مجال الدراسة سيكون محصورا في سكان هذا التجمع الحضري . ولقد توصلت هذه الدراسة لمجموعة من النتائج بعد إجراء الدراسة الامبريقية ، حيث وجدنا أنه لحد ما وجود تهيئة حضرية عند القيام بعملية الإسكان في هذا الحي ، لكنها مست د جوانب وأهملت بعض الجوانب الأخرى ، فمن ناحية الجوانب التي مستها التهيئة الحضرية نجد الماء والكهرباء مثلا ، أما من ناحية الطرقات هناك نقائص على مستوى هذه الأخيرة ، أما بالنسبة للنقل فهناك تباين في النتائج بين حالة توفره ومدى تحسنه . ه Abstract: The urban setting is the various programs and policies put competent authorities to regulate urban area including urban housing process , which is a housing and Ocean found it and which is available on the original service centers necessary and which provide proper social life of the community members , bringing the urban setting is to ensure the provision of these widgets and utilities, if absent absent with the terms of comfort and luxury . The reason for choosing this subject is reflected in the buoyant urban configuration problem related to housing on top of the issues that have emerged in our country , as well as the emergence of many of the problems faced by the Algerian city , as embodied the importance that the Housing and Urban initialization problem is one of the issues that plague the state and officials by virtue of association essential human needs . Due to the start of the topic of social reality was descriptive and analytical approach is best suited to the subject of the study , as this study seeks to describe the research community characteristics and try to highlight the relationship between the different variables , this study was conducted in the neighborhood of 08 May 1945 the valley , specifically in the residential community featuring 1388 condo is located in the the eastern side of the neighborhood and from the field of study will be confined to the urban population of this assembly. This study has reached a set of results after the empirical study , we find that in this neighborhood there creating urban When you do a housing but touched aspects and neglected some of the other aspects , the one hand, aspects that touched the water and urban configuration and electricity , we find that they present , either in terms of roads there are imperfections on the level of the latter , while for the transfer , there are discrepancies in the results between the case provided and the extent of his recovery.
دراسة ميدانية بحي 08 ماي 1945 بالوادي
مذكرة ماستر علوم اجتماعية تخصص علم اجتماع حضري
Keywords: السكن، التهيئة الحضرية; Logement, urbanisation; Housing, urbanization